Female California mouse scent marking behavior and its implications for the pair bond - Kumerow, Marie (My University, 2013)
Scent marking has been shown to be an active form of communication for male mice in claiming territory, advertising for females, and mate guarding. Yet little is known about how females use scent marking behaviorally. California mouse is a traditionally monogamous species. Pair bonding in male Caliornia mice has shown to reduce advertisement through scent marking to novel females. This study aims to further explore the nature of the pair bond in the female California mouse through interactions with her mate relative to a naive male. Females were exposed to a pretest, a control condition, a substrate previously marked by a naive male and one marked by their mate. Size, volume, distribution and overmarkings were assessed in a preliminary analysis. Early data shows that females may preferentially overmark their mates to a naive male. This could further explain for the scent marking strategies employed by female mice.
Keywords: Psychology; Zoology; Genetics